The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1088/0264-9381/22/9/009
|View full text |Cite
|
Sign up to set email alerts
|

Static axisymmetric spacetimes with prescribed multipole moments

Abstract: In this article we develop a method of finding the static axisymmetric space-time corresponding to any given set of multipole moments. In addition to an implicit algebraic form for the general solution, we also give a power series expression for all finite sets of multipole moments. As conjectured by Geroch we prove in the special case of axisymmetry, that there is a static space-time for any given set of multipole moments subject to a (specified) convergence criterion. We also use this method to confirm a con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
82
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(83 citation statements)
references
References 14 publications
1
82
0
Order By: Relevance
“…It has been shown that the spacetime is uniquely determined by its multipole moments [133][134][135]: in other words, they completely characterize the spacetime geometry outside any stationary body. It has also been shown (in the axisymmetric case) that it is possible to reconstruct the full spacetime from any "well-behaved" set of relativistic multipole moments [136,137].…”
Section: Multipolar Expansions In Newtonian Gravity and In General Rementioning
confidence: 99%
“…It has been shown that the spacetime is uniquely determined by its multipole moments [133][134][135]: in other words, they completely characterize the spacetime geometry outside any stationary body. It has also been shown (in the axisymmetric case) that it is possible to reconstruct the full spacetime from any "well-behaved" set of relativistic multipole moments [136,137].…”
Section: Multipolar Expansions In Newtonian Gravity and In General Rementioning
confidence: 99%
“…the Quadrupole Solution itself, and more recently in [11], [12] a method has been proposed for obtaining the general terms of the series (the coefficients a n ) that define the Pure 2 N -pole Solutions. In fact, the general term of the series corresponding to the gravitational Dipole and the solutions with Monopole plus any other 2 N -pole moment are written specifically.…”
Section: Calculation Of Msa Coordinates For Any Multipole Solutionmentioning
confidence: 99%
“…Moreover, the Weyl family of solutions depends on arbitrary constants, a n , in principle without any physical criteria to choose one or another solution from them, whereas the function u would allow us to deal, in a very simple form, with the Relativistic Multipole Solutions. This has been the aim of some authors and their works devoted to obtain solutions of the Einstein vacuum equations with a finite number of prescribed RMM [7,9,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The stellar shape affects the gravitational field outside the source, which controls various NS observables. The exterior gravitational field can be described through a multipolar decomposition (Backdahl & Herberthson 2005;Backdahl 2007), just as when describing the exterior electromagnetic field of a charged object with multipole moments.…”
Section: Introductionmentioning
confidence: 99%